Estudo educacional das características sintáticas dos títulos de textos publicitários - Tkhorikov, Boris A.; Vinnik, Alina E.; Osadchaya, Svetlana M.; Gerasimenko, Olga A.; Dolinsky, Nikolai I. (Revista EntreLinguas, 2022)
The article describes the results of the educational study of assessing the perception of various headings of advertising texts. The study involved 12 subjects who, using Pupil eyewear glasses and software from Pupil (Germany), looked at 6 different headings oriented to the left or right hemisphere of the brain. According to the results of processing the observation results, the possibility of enhancing the attractiveness of the headings through the use of syntax focused on the preferential activation of one of the cerebral hemispheres was not confirmed. Conclusions are drawn on the advisability of using short exclamation or unallocated types of promotional offers.